Immunosuppressive mechanisms and therapeutic targeting of regulatory T cells in ovarian cancer - Li, Jing; Huang, Haojun; Xie, Renxian; Yang, Rongying; Wang, Haitao; Wan, Li (Frontiers in Immunology, 2025)
Ovarian cancer remains the most lethal gynecologic malignancy, largely due to its late-stage diagnosis and immunosuppressive tumor microenvironment (TME). A key mediator of immune evasion in ovarian cancer is the infiltration and activation of regulatory T cells (Tregs), which suppress antitumor immunity and foster therapeutic resistance. Emerging therapeutic strategies to target Tregs—such as cytokine modulation, checkpoint blockade, metabolic inhibitors, and epigenetic regulators—are critically evaluated for their potential to restore antitumor immunity. This review synthesizes recent advances in understanding how the ovarian TME shapes Treg biology, highlighting mechanisms such as cytokine signaling, chemokine-driven recruitment, metabolic reprogramming, and immune checkpoint interactions, as well as the phenotypic and functional heterogeneity of tumor-infiltrating Tregs, including tissue-resident and follicular subsets, and their clonal expansion in response to tumor antigens. By elucidating the dynamic crosstalk between Tregs and the ovarian TME, this review provides a framework for developing novel immunotherapies to overcome Treg-mediated immunosuppression and improve clinical outcomes.